A comparison of short-term outcomes of neck dissection for head and neck cancers using Thunderbeat™, LigaSure™ or treatment without an energy-based device: A case controlled study. (October 2018) - Suzuki, Kensuke; Shimizu, Minaki; Sakagami, Tomofumi; Yagi, Masao; Fujisawa, Takuo; Sawada, Shunsuke; Kanda, Akira; Kobayashi, Yoshiki; Iwai, Hiroshi
Abstract: Objective: The aim of this study was to evaluate the efficacy of the new energy-based device Thunderbeat in neck dissection (ND) for head and neck cancer. Materials and methods: We retrospectively examined 95 consecutive patients who underwent ND for head and neck squamous cell carcinoma between April 2013 and March 2018. The patients were divided into three groups: ND without the energy-based device (control group), ND using the LigaSure Small Jaw (LS group), and ND using the Thunderbeat Open Fine Jaw (TB group). The outcomes were compared among the three groups, as measured by the duration of ND (dissection time), blood loss during ND, and postoperative complications. We also analyzed the factors that may influence dissection time using multivariate analysis. Results: Compared to the control group, dissection time was found to be significantly shorter in both energy-based device groups (LS group and TB group) (96.4, 71.1, and 66.0 min, respectively, p = 0.0015) by univariate analysis. Blood loss during ND did not differ significantly among the three groups. Multivariate analysis showed that ND using the Thunderbeat as well as elderly patients (70 years and over), less extensive surgery (3 or fewer neck levels), and absence of extracapsular invasion were independently and significantly associated with shorter dissection time (p = 0.0069, 0.0337, <0.0001, and 0.0015, respectively). The incidence of postoperative complications in the LS group (20%) tended to be higher than those in the other groups (5.6% in the control group and 3.4% in the TB group), although the differences were not significant. Conclusion: ND for head and neck cancers using the Thunderbeat is a safe and reliable method in terms of duration of dissection without increasing postoperative complications. Highlights: The efficacy of the new energy-based device Thunderbeat in neck dissection was investigated. The Thunderbeat can reduce dissection time without increasing postoperative complication. Neck dissection using the Thunderbeat is a safe and reliable method.